Exploring the acceptability of wildlife tourism joint ventures in wildlife management areas, Northern Tanzania - Kulunge, Salum R.; Mariki, Sayuni; Roe, Dilys; Snyman, Susan (Sue); Dickman, Amy; Sibanda, Lovemore; Hare, Darragh; Mbije, Nsajigwa (Frontiers in Conservation Science, 2026)
PurposeThis study investigates the acceptability of wildlife tourism joint ventures (JVs) among rural communities in northern Tanzania’s Wildlife Management Areas (WMAs). These partnerships between communities and external investors aim to conserve biodiversity and deliver sustainable socioeconomic benefits. Guided by the Cognitive Hierarch Model (CHM), the research examines how values, beliefs and contextual experiences shape community judgements of JVs.MethodsWe employed a mixed-methods approach, including household surveys with 548 respondents across nine villages (three from each of the Burunge, Enduimet and Randilen WMAs) and 20 Key Informant Interviews. The surveys captured respondents’ perceptions of JV benefits, conservation-related factors and demographic information, while key informant interviews provided deeper contextual perspectives on wildlife tourism partnerships. We analyzed the quantitative data using an ordinal cumulative link mixed model and applied thematic analysis to the qualitative data to determine the acceptability of JVs in WMAs.ResultsWe found that community acceptability of JVs is positively influenced by perceived socio-economic benefits, including financial opportunities, support for public infrastructure, access to employment in tourism facilities and support for local microenterprises. However, limited recognition or awareness of investor contributions to wildlife protection can reduce community willingness to accept and support JVs. Education and positive expectations of tourism growth further enhance acceptability, while negative experiences related to conservation foster skepticism. Observed variations across WMAs and among households highlight the need for place-based governance and locally tailored approaches to ensure that JV outcomes align with community priorities.Discussion/originalityThis study offers a novel application of CHM to the context of wildlife tourism, moving beyond socioeconomic impact assessments to explore psychological and contextual drivers of community acceptability of JVs. Our findings inform policy, conservation and investment strategies aimed at fostering household-level engagement strategies that can ensure equitable access to benefits, strengthen trust and sustainable wildlife tourism JVs, with implications for enhancing rural community participation, economic growth and conservation outcomes.